IITA Gender Responsive Breeding Training - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
As part of activities under the Accelerated Breeding (ABI) and Market Intelligence and Product Profiling (MIPPI) initiatives, IITA in conjunction with the Accelerated Varietal Improvement and Seed Delivery of Legumes and Cereals in Africa (AVISA), AFRICA YAM and NEXTGEN Cassava Project organized a 3-day Gender-Responsive Breeding training. The training was anchored by Gender Specialist Martina Cavicchioli, Associate Social and Gender Scientist Béla Teeken, Senior Gender Research Associate Olamide Deborah Olaosebikan, Gender Research Post-Doctoral Fellow Millicent Liani, HarvestPlus Cassava Breeder Elizabeth Parkes, and Cassava Breeder Abolore Bello.